Ticket Sales and Violent Content in Popular Movies. Issue 8 (2nd August 2020) - Barranco, Raymond E.; Rader, Nicole E.; Trinh, Maria T.
ABSTRACT: Recent research has found a link between the presence of violent content, movie ratings, and ticket sales, but has left several questions unanswered. The current study attempts to answer these questions by examining the level of adult content in 2, 094 popular movies between 1992 and 2012. We find that the amount of violent content is a significant predictor of ticket sales, but only in non-R rated movies. Furthermore, we find evidence that violent content has been increasing in non-R rated movies and this increase is likely due to changes in MPAA ratings standards. We discuss the implications of our findings.